Effects of an industrial graphene grade and surface finishing on water and oxygen permeability, electrical conductivity, and mechanical properties of high-density polyethylene (HDPE) multilayered cast films. (June 2022) - Ferreira Junior, José Carlos; Moghimian, Nima; Gutiérrez, Giovanna; Helal, Emna; Ajji, Abdellah; Barra, Guilherme Mariz de Oliveira; Demarquette, Nicole R.
Abstract: Graphene-based composites are promising candidates to improve properties in flexible packaging to protect electronic devices. However, the literature hardly addresses the industrial scale requirements. In this context, high-density polyethylene (HDPE), a common packaging material, and an industrial grade graphene (G) were used to prepare multilayered composites by cast film coextrusion, a flexible-packaging-industry compatible technique. The effects of G content and surface finishing on HDPE films' properties were investigated. Experimental results showed that a maximum permeability reduction of 43% at 0.5 wt% of G was achieved. Such result was associated with a good dispersion efficiency and with the filler's aspect ratio. However, as the concentration of G increased both barrier and mechanical properties worsened due to a poor dispersion of G within the composite. Additionally, it was found that surface finishing induced defects increasing permeability despite improvements in visible light transmittance and reduction of surface roughness. These defects can be successfully prevented using a proper design of layers during coextrusion. In summary, the present study showed the feasibility of G-based flexible packaging film applications at an industrial scale. The importance of G dispersion and of layer design to achieve improved barrier properties should be emphasized. Graphical Abstract: ga1 Highlights: Industrial grade graphene can be used for flexible packaging applications. 0.5 wt% of industrial grade graphene reduced the oxygen permeability in 43%. Layer design allows to overcome filler dispersion shortcomings.